Building the Sustainable Self-Reliance on Children Behaviour During the Pandemic through the Logical Framework Approach - Maspul, Kurniawan Arif; Amalia, Fina (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
During the pandemic in the last two years, it has evolved a challenge for teachers and parents and for developing children’s thinking. At an early age where they should be able to learn constantly through the school and home environment, they suddenly descend into a situation of uncertainty which makes the limitations of developing their behaviour. As the nation’s best generation hopefuls, it is necessary to introduce children through a logical framework to have independence, especially in dealing with uncertain situations at this time. The authors are straining how children can apply it through direct guidance from parents and teachers with hybrid guidance through this framework. Through qualitative concepts accompanied by interviews and observations in SD Islam & Tahfidz Ibnu Umar Tangerang Selatan, parents feel the progress of their children’s way of thinking in dealing with time and making more use of it positively through their daily activities and adding self-confidence, especially in their independence in making choices in the use of time.